2017
DOI: 10.15761/cmid.1000119
|View full text |Cite
|
Sign up to set email alerts
|

Increased RANKL/OPG Ratio and Sclerostin in Patients with Septic Shock

Abstract: We report an increased RANKL/OPG ratio and increased sclerostin levels in patients with septic shock one day after admission compared to healthy subjects, indicating an increased risk for bone loss in survivors of septic shock. No increase in RANKL/OPG ratio was observed in patients treated with hydrocortisone during septic shock.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…We found that the level of serum RANKL was increased (Figure A) and OPG, P1NP, OCN, Ca 2+ , and ALP levels were decreased in the OVX group (Figure B–D, Figure S1F–H). The ratio of RANKL/OPG played a key role in regulating osteoclast differentiation and affecting the balance between bone formation and bone resorption . Ovariectomy elevated the ratio of RANKL/OPG (Figure C).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that the level of serum RANKL was increased (Figure A) and OPG, P1NP, OCN, Ca 2+ , and ALP levels were decreased in the OVX group (Figure B–D, Figure S1F–H). The ratio of RANKL/OPG played a key role in regulating osteoclast differentiation and affecting the balance between bone formation and bone resorption . Ovariectomy elevated the ratio of RANKL/OPG (Figure C).…”
Section: Resultsmentioning
confidence: 99%
“…The ratio of RANKL/OPG played a key role in regulating osteoclast differentiation and affecting the balance between bone formation and bone resorption. 32 Ovariectomy elevated the ratio of RANKL/OPG (Figure 3C). mEVs could restore bone turnover and improve bone resorption in OVX mice (Figure 3A Furthermore, the effect of mEVs on osteoclast formation was investigated in vitro.…”
Section: Mevs Prevented Bone Lossmentioning
confidence: 94%